Predictive effect of sustainable dietary and literacy patterns on metabolic syndrome and diabetes risk in Turkish adults: Mediterranean diet, sustainable healthy eating behaviors, and sustainable food literacy perspective - İncedal Irgat, Serap and Bakırhan, Hande and Bakırhan, Yunus Emre (Frontiers in Medicine, 2025)
BackgroundFood literacy and sustainable patterns may be associated with metabolic disease risk. Therefore, it is important to determine the potential impact of sustainable dietary concepts, as well as the development of food literacy, on the risk of metabolic syndrome (MetS) and diabetes. The aim of this study was to investigate the associations of sustainable dietary concepts and sustainable food literacy with the risk of MetS and diabetes in adults.MethodsThis study included a total of 6,364 healthy Turkish adults. To determine the extent to which sustainable dietary concepts affect MetS and diabetes in participants, the status of participants was assessed with the following scales: the Sustainable and Healthy Eating Behaviors Scale (SHEBS), the Sustainable Food Literacy Scale (SFLS), the Mediterranean Diet Adherence Screener (MEDAS), the Metabolic Syndrome Index (MSI), the Metabolic Syndrome Research Form (MSAF), and the Finnish Diabetes Risk Score (FINDRISC).ResultsMost participants were found to have a low risk of diabetes (62.6%), 49.8% had a moderate risk of MetS (based on the MSAF), and 21.3% had a high risk of MetS (based on the MSI). Participants with a high level of MEDAS had a lower MSI score than did those with a moderate or low level (p < 0.001), whereas those with a low level of MEDAS had a significantly higher MSAF score than did those with a moderate or high level (p < 0.001). As participants’ MSI and FINDRISC levels decreased, their SHEBS and SFLS scores significantly increased (p < 0.001). As MSAF levels increased, participants’ MEDAS scores significantly decreased (p < 0.001). SFLS and MEDAS had a negative and significant effect on the MSAF (β = −0.03, β = −0.04; p < 0.05, respectively), whereas SHEBS had a stronger and negatively significant effect (β = −0.08; p < 0.001). The MEDAS (β = −0.03; p = 0.007), SHEBS (β = −0.08; p < 0.001), and especially the SFLS (β = −0.13; p < 0.001) were found to be negative and significant predictors of MetS risk (for MSI), whereas the SFLS was a negatively significant predictor of diabetes risk (β = −0.11; p < 0.001).ConclusionThe effects of sustainable healthy eating behaviors, sustainable food literacy and Mediterranean diet on preventing the risk of MetS are significant, and the most important negative predictor of diabetes risk is SFLS.